Tyrosine 192 within the SH2 domain of the Src-protein tyrosine kinase p56(Lck) regulates T-cell activation independently of Lck/CD45 interactions - Kästle, Matthias (Cell Commun Signal, 2020)
BACKGROUND: Upon engagement of the T-cell receptor (TCR), the Src-family protein tyrosine kinase p56Lck phosphorylates components of the TCR (e.g. the TCRζ chains), thereby initiating T-cell activation. The enzymatic activity of Lck is primarily regulated via reversible and dynamic phosphorylation of two tyrosine residues, Y394 and Y505. Lck possesses an additional highly conserved tyrosine Y192, located within the SH2 domain, whose role in T-cell activation is not fully understood. METHODS: Knock-in mice expressing a phospho-mimetic (Y192E) form of Lck were generated. Cellular and biochemical characterization was performed to elucidate the function of Y192 in primary T cells. HEK 293T and Jurkat T cells were used for in vitro studies. RESULTS: Co-immunoprecipitation studies and biochemical analyses using T cells from Lck(Y192E) knock-in mice revealed a diminished binding of Lck(Y192E) to CD45 and a concomitant hyperphosphorylation of Y505, thus corroborating previous data obtained in Jurkat T cells. Surprisingly however, in vitro kinase assays showed that Lck(Y192E) possesses a normal enzymatic activity in human and murine T cells. FLIM/FRET measurements employing an Lck(Y192E) biosensor further indicated that the steady state conformation of the Lck(Y192E) mutant is similar to Lck(wt). These data suggest that Y192 might regulate Lck functions also independently from the Lck/CD45-association. Indeed, when Lck(Y192E) was expressed in CD45(−/−)/Csk(−/−) non-T cells (HEK 293T cells), phosphorylation of Y505 was similar to Lck(wt), but Lck(Y192E) still failed to optimally phosphorylate and activate the Lck downstream substrate ZAP70. Furthermore, Lck(Y19E) was recruited less to CD3 after TCR stimulation. CONCLUSIONS: Taken together, phosphorylation of Y192 regulates Lck functions in T cells at least twofold, by preventing Lck association to CD45 and by modulating ligand-induced recruitment of Lck to the TCR. MAJOR FINDINGS: Our data change the current view on the function of Y192 and suggest that Y192 also regulates Lck activity in a manner independent of Y505 phosphorylation.